2014
DOI: 10.4236/aim.2014.47046
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of <i>Escherichia coli</i> O157:H7 Virulence Factors: The First 25 Years and 13 Genomes

Abstract: Escherichia coli O157:H7 is a human pathogen that was first identified from a foodborne outbreak in 1982, and in the 25 years that followed, many new strains were identified and emerged in numerous outbreaks of human disease. Extensive research has been conducted to identify virulence factor genes involved in the pathogenesis of E. coli O157:H7 and many genome sequences of E. coli O157:H7 strains have become available to the scientific community. Here, we provide a comprehensive overview of the research that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 107 publications
(198 reference statements)
0
22
0
Order By: Relevance
“…The hypotheses based on a “commensal” origin pertain to D6-117.07, P4, VL2732 and VL2874, which very likely belong to the mainly commensal A. By contrast, highly virulent O157:H7 strains are known to possess specific virulence factors, including toxins, molecules responsible of the formation of secretion systems, and molecules involved in attaching/effacing lesions [ 70 , 71 ]. Nevertheless, a specific search for candidate virulence genes showed that strain D6-113.11 was clearly different from the O157:H7 Sakai strain included in our comparison.…”
Section: Discussionmentioning
confidence: 99%
“…The hypotheses based on a “commensal” origin pertain to D6-117.07, P4, VL2732 and VL2874, which very likely belong to the mainly commensal A. By contrast, highly virulent O157:H7 strains are known to possess specific virulence factors, including toxins, molecules responsible of the formation of secretion systems, and molecules involved in attaching/effacing lesions [ 70 , 71 ]. Nevertheless, a specific search for candidate virulence genes showed that strain D6-113.11 was clearly different from the O157:H7 Sakai strain included in our comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the major STEC genotype isolated from 12 months old calves was stx2 . Two stx genes encode Shiga toxins which are stx1AB and stx2AB , and it has been reported that Stx2 is associated with more severe human infections [ 20 , 21 ]. The predominance of stx2 genotype in older calves is noteworthy, although the overall STEC prevalence declined when animals aged, because Stx2 is 1000 times more toxic than Stx1 as shown previously in animal models [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent Shiga toxin producing E . coli O157:H7 outbreak strains have been found to carry two copies of the stx2AB gene cluster instead of one of the stx1AB and one of the stx2AB clusters each, making them more virulent than the isolates carrying only the stx1AB gene cluster, due to lack of competition for GB3 binding [ 20 , 21 ]. Taken together, although the prevalence of STEC was lower in older animals, the calves were carrying more pathogenic STEC, suggesting further STEC genotyping is necessary for proper risk assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of E. coli O157:H7 to cause disease is associated with production of Shiga toxins, which is controlled by stx1 and stx2 genes and other virulence factors (Bai, Shi, & Nagaraja, 2010;Reiland, Omolo, Johnson, & Baumler, 2014). Moreover, culture conditions, such as temperature, acidic environment, and nutrient levels, can affect the expression of bacterial virulence genes (Allen et al, 2008;Yin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%